Role of tumor mutational burden in patients with urothelial carcinoma treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Wang, Zhe; Huang, Danxue; Li, Su; Ke, Liyuan (Frontiers in Immunology, 2025)
BackgroundThe predictive value of tumor mutation burden (TMB) on the efficacy of immunotherapy has been confirmed in multiple cancer types in previous studies. For urothelial carcinoma (UC) patients treated with immune checkpoint inhibitors (ICIs), whether TMB is a suitable biomarker to predict the benefit of ICIs remains a matter of much debate. We conducted this meta-analysis to evaluate the role of TMB in patients with UC treated with ICIs.MethodsTwo investigators independently searched the literature, screened eligible studies, extracted valid data, and scored quality assessments. Meta-analyses of the effect size hazard ratio (HR) for overall survival (OS) and progression-free survival (PFS), and effect size odds ratio (OR) for objective response rate (ORR) were performed and visualized with forest plots using the STATA14.0 software. The statistical difference in benefit from ICIs for UC patients between the high TMB group and the low TMB group was significant when the p-value <0.05. Sensitivity analysis and publication bias further verified the stability and reliability of statistical results.ResultsA total of 2,499 patients from 14 studies were included in this meta-analysis. The results indicated that UC patients with high TMB showed significantly longer OS and PFS than those with low TMB after ICI treatment (OS: HR 0.69, 95% CI 0.62, 0.76, p < 0.05; PFS: HR 0.67, 95% CI 0.59, 0.76, p < 0.05). The high TMB group exhibited a superior response to ICIs than the low TMB group, with no significant difference (OR 1.64, 95% CI 0.94, 2.86, p = 0.08). The results were stable and reliable, with no publication bias.ConclusionsThis meta-analysis demonstrated that UC patients with high TMB exhibited significantly longer survival than those with low TMB after ICI treatment. TMB may be a favorable predictor for UC immunotherapy in future clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025642602.